Respuesta :

Answer:

Step-by-step explanation:

-7x-2y=-13

x-2y=11

(subtract the first inequality from the second)

-7x-x = -8x

-2y-(-2y) = 0

-13-11= -24

-8x=-24

x=3

(now place the x value into the second inequality)

3-2y=11

-2y=11-3

-2y=8

y=-4

x=3

y=-4

Answer: x=3, y= -4

Steps: The two equations are," -7x-2y=-13 " and " x - 2y = 11 "

Let's take the 2nd equation and find for x

x - 2y = 11

x= 11 + 2y

Now place the value of x in the first equation:

-7(11+2y) - 2y = -13

-77 - 14y - 2y = -13

- 16y= -13 + 77

y= 64/-16

y= -4

Now that you found the value of y, place it again on the 2nd equation:

x - 2(-4) =11

x + 8= 11

x=11-8

x= 3

Brainliest pls if i am correct!